2008
DOI: 10.5194/adgeo-14-99-2008
|View full text |Cite
|
Sign up to set email alerts
|

Hydro-seismic-acoustical monitoring of submarine earthquakes preparation: observations and analysis

Abstract: Abstract. The results of laboratory experiments on rock sample destruction and the observation data obtained from several series of the hydro-acoustic observations in which the researchers succeeded to register the signals in the critical stage of the earthquake (EQ) preparation were compared. According to theoretical research (Alekseev et al., 2001) two distinct dilatant zones occur in the EQ preparation stage. The first one is located around the source and the second one represents the near-surface dilatant … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 5 publications
2
2
0
Order By: Relevance
“…The most vivid such effects are observed at the final stage of earthquake preparation. This result agrees well with the results of mathematical models (Alekseev et al, 2001;Dobrovolsky, 2000;Okada, 1985;Vodinchar et al, 2007) and natural experiments (Agnew and Wyatt, 2003;Berardino et al, 2002;Dolgikh et al, 2007;Sasorova et al, 2008). These authors showed that amplification of a deformation process occurs during earthquake preparation in the regions of their epicenters at distances of up to several hundreds of kilometers.…”
Section: Discussionsupporting
confidence: 81%
See 2 more Smart Citations
“…The most vivid such effects are observed at the final stage of earthquake preparation. This result agrees well with the results of mathematical models (Alekseev et al, 2001;Dobrovolsky, 2000;Okada, 1985;Vodinchar et al, 2007) and natural experiments (Agnew and Wyatt, 2003;Berardino et al, 2002;Dolgikh et al, 2007;Sasorova et al, 2008). These authors showed that amplification of a deformation process occurs during earthquake preparation in the regions of their epicenters at distances of up to several hundreds of kilometers.…”
Section: Discussionsupporting
confidence: 81%
“…A seismotectonic process is constantly going on there, accompanied by stronger rock deformations; thus, stronger effects in geoacoustic emissions should be registered. It is confirmed by the results of investigations in different seismically active regions (Gregori et al, 2005(Gregori et al, , 2010Kuptsov, 2005;Levin et al, 2010;Morgunov et al, 1991;Paparo et al, 2002;Sasorova et al, 2008), where geoacoustic emission anomalies in the frequency range of the first kilohertz, which preceded strong earthquakes, were determined. The papers (Alekseev et al, 2001;Dobrovolsky, 2000;Okada, 1985;Vodinchar et al, 2007) present the models, which show the deformation nature of the appearance of such anomalies, and the paper (Dolgikh et al, 2007) experimentally confirms the relation of the geoacoustic emission anomaly to the dynamics of geodeformation processes before an earthquake.…”
Section: Introductionsupporting
confidence: 70%
See 1 more Smart Citation
“…In the wide range of dislocation scales and the corresponding wave lengths of radiated oscillations, we can distinguish three emission frequency ranges, the investigation of which differs both in problems and in observation means. The infrasound frequency range (fractions–units of hertz) is applied to record earthquakes and to estimate their characteristics, and to monitor nuclear tests in seismic measurements [ 1 , 2 , 3 ]. The ultrasound frequency range from 20–30 kHz to the first megahertz is used in the industry for the early detection of fractures, material creep testing, detection of hidden defects in different types of constructions including the elements of rockets, airplanes, bridges and others as well as in geophysics during the laboratory deformation of rock samples to research fracture formation mechanisms [ 4 , 5 , 6 ].…”
Section: Introductionmentioning
confidence: 99%